ANALISIS KUALITAS LAYANAN PENGUSAHA PENGURUSAN JASA KEPABEANAN (PPJK) PADA PERUSAHAAN FREIGHT FORWARDING MENGGUNAKAN SERVICE QUALITY (SERVQUAL) - Naura, Rifda Tsabita; Praharsi, Yugowati; Bawole, Alfred (Program Studi Teknik Industri, Fakultas Teknik Universitas Tarumanagara, 2024)
The increasing trend in import-export activities demands optimal service, especially in customs clearance. Exporters and importers who cannot manage these processes can delegate authority to Customs Clearance and Forwarding Service Providers (PPJK). Company data reveals that the number of Sea Freight service users as exporters from January to December 2022 is higher than the number of service users employing PPJK. The research aims to analyze the quality of PPJK services in Freight Forwarding companies to provide services aligned with customer expectations. This study employs questionnaires and the Service Quality (Servqual) method to assess customer satisfaction, Importance Performance Analysis (IPA) to gauge company service quality, and Potential Gain in Customer Value (PGCV) to prioritize improvements. The Servqual results indicate that 33 attributes show negative gap values, indicating customer dissatisfaction, while 5 attributes exhibit positive ones. The IPA matrix results depict 7 attributes in quadrant I, representing low service quality performance but high customer expectations. The PGCV analysis prioritizes improvement in attributes U3, T1, U1, RS3, A4, CC1, and S3. The recommended improvements for the company include organizing customer gatherings, developing a web-based application, enhancing communication, providing problem-solving assistance, increasing staffing, delivering explanations in simple language, and strengthening monitoring processes.